The Use of a Modest Alcohol Meter - Maria Agatha Hertiavi; Putut Marwoto; Retno Sri Iswari; Edy Cahyono (Jurnal Penelitian Pendidikan IPA, 2021)
During the pandemic, healthy life behavior is needed in an attempt to reduce the transmission risk.Â  One of them could be done by washing hands. Various human activities may not allow them to wash their hands frequently, for example, using hand sanitizer to wash hands. Hand sanitizer or Isopropyl based alcohol are recommended materials by WHO to clean bacteria on hands. Storing hand sanitizer for a longer time leads to inaccurate quality of the hand sanitizer to the written quality on the package. A simple alcohol meter is designed to test the liquid percentage of hand sanitizer or Isopropyl Alcohol (IPA) based alcohol. The required materials are easy to get from the surrounding environment. Thus, this device could be established at home without ignoring the health protocol. Although it has strength IPA-based alcohol or hand sanitizer is also risky if it is incorrectly used